Exploring the Rural Eco‐Economy: Beyond Neoliberalism. Issue 4 (26th July 2016) - Marsden, Terry
Abstract: Rural areas become central sites for the development of the post‐carbon transition, yet this is a highly contested and contingent process whereby neo‐liberal models of development and framings compete with the emergence of the alternative circular eco‐economy. The article argues for a grounded conceptual and empirical approach in tracing this overall process of sustainable place‐making. It explores three key highly contested dimensions: reflexive governance, distributed eco‐economies, and re‐financialisation, arguing that such explorations are critical in developing more sustainable rural‐urban functionalities for the necessary post‐ carbon and post‐neoliberal transition.